2014
DOI: 10.1186/s40536-014-0007-2
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative synthesis of the immigrant achievement gap across OECD countries

Abstract: Background: While existing evidence strongly suggests that immigrant students underperform relative to their native counterparts on measures of mathematics, science, and reading, country-level analyses assessing the homogeneity of the immigrant achievement gap across different factors have not been systematically conducted. Beyond finding a statistically significant average achievement gap, existing findings show considerable variation. The goal of this quantitative synthesis was to analyze effect sizes which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…Because the target population of international assessments includes only students currently enrolled in school, countries with the most rapidly expanding school access may appear to have growing SES achievement gaps due to the inclusion of relatively disadvantaged populations. Additionally, increasing global migration has led to a larger share of immigrant students enrolled in schools in many countries, which could lead to growing SES achievement gaps in those countries, to the extent that immigrant students are lower-achieving and lower-SES than native-born students (Andon, Thompson, and Becker 2014).…”
Section: Explanations For Trends In Ses Achievement Gapsmentioning
confidence: 99%
“…Because the target population of international assessments includes only students currently enrolled in school, countries with the most rapidly expanding school access may appear to have growing SES achievement gaps due to the inclusion of relatively disadvantaged populations. Additionally, increasing global migration has led to a larger share of immigrant students enrolled in schools in many countries, which could lead to growing SES achievement gaps in those countries, to the extent that immigrant students are lower-achieving and lower-SES than native-born students (Andon, Thompson, and Becker 2014).…”
Section: Explanations For Trends In Ses Achievement Gapsmentioning
confidence: 99%
“…Additionally, Barb and Beal [21] pointed out, word problems written in complex language is rated as mathematically more difficult to solve than the same problems written in simpler language. Individuals who are not fluent in English may perform more poorly than their peers in other subjects that are not directly related to the language [22]. This brings the issue of language as a barrier to mathematics word problem solving for English as second language (ESL) students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, the significant disadvantage in mathematical literacy performance was still evident among immigrant students in PISA 2012. Andon et al (2014) did a quantitative synthesis of the immigrant achievement gap across OECD countries using data from both TIMSS and PISA between 2000 and 2009. The study found a significant mean effect size for mathematics (d = 0.38).…”
Section: Immigrant Background Equitymentioning
confidence: 99%